The Effect of Work Environment, Work Ethic and Organizational Culture on Employee Performance - Ngebursian, Roberthus; Latupapua, Conchita.V.; Risambessy, Agusthina (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Employees who have a high work ethic are reflected in their behavior, such as liking to work hard, being fair, not wasting time during working hours, wanting to give more than what is indicated, willing to work together, respecting colleagues. This research aims to analyze and explain the influence between work ethic, organizational culture and employee performance. Work environment variables as mediation. The research object was carried out at the Pulau-Pulau Aru District Office, the sample determination method used the saturated sample technique with a sample size of 30 people. The data analysis method uses Path Analysis. The research results prove that: Work ethic has a significant effect on employee performance. Organizational culture has a significant effect on employee performance. Work ethic has a significant influence on the work environment. Organizational culture has a significant effect on employee performance. The work environment has a significant effect on employee performance. Work ethic has a significant effect on employee performance, mediated by the work environment. Organizational culture has a significant effect on employee performance, mediated by the work environment.